Sejarah Revolusi Industri - Dito Fernando; Fahruddin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The purpose of writing this book review article: (1) to explain the Condition of British Society Before the Industrial Revolution. (2) describes the Industrial Revolution. (3) explaining the impact of the industrial revolution. The results of this study found that (1) the condition of English society before experiencing the industrial revolution first experienced the dark ages where the church controlled many aspects of life. (2) the industrial revolution is a change in the replacement of human power by machine power. (3) the impact of the industrial revolution affected the social, economic, and political fields.